Sosialisasi Penggunaan Aplikasi Origin dan ImageJ untuk Analisis Sampel Material pada Mahasiswa Program Studi Fisika FST Universitas Jambi - Pujaningsih, Febri Berthalita; Deswardani, Frastica; Alrizal, Alrizal; Pebralia, Jesi; Afrianto, M Ficky; Maulana, Lucky Zaehir; Anggraeni, Rista Mutia; Samsidar, Samsidar; Fendriani, Yoza; Hamdi, Husnul; Resta, Ichy Lucya (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
In the digital era, the ability to process and analyze experimental data has become an important skill in the field of materials science and engineering. Origin is a commercial software widely used for numerical data analysis and scientific visualization, while ImageJ is open-source software that functions in image processing of microscopic characterization results. Considering the importance of mastering both software, a socialization activity and basic training on the use of Origin and ImageJ was held for students of the Physics Study Program, Faculty of Science, University of Jambi. This activity aims to enable students to operate the software in processing research data independently and in accordance with scientific publication standards. Evaluation of the training was carried out by assessing the level of student understanding, which showed an increase in basic skills in using Origin for quantitative data analysis and ImageJ for digital image analysis.